Synchrony of neuromodulatory systems during NREM sleep - Sasa Teng; Angie N. Maldonado Rodriguez; Ruizhi Wang; Xinyue Chen; Yueqing Peng (Proceedings of the National Academy of Sciences, 2025)
Neuromodulatory systems play an essential role in regulating brain states and functions. The canonical view is that the release of monoamines including norepinephrine (NE) and serotonin (5-HT) is high during wakefulness and attenuated during sleep, particularly during rapid eye movement (REM) sleep, whereas the cholinergic system is active during both wakefulness and REM sleep and quiescent during non–REM (NREM) sleep. Recent studies have revealed a slow and rhythmic release pattern of neuromodulators during NREM sleep that drives infraslow oscillation (ISO) (0.02 to 0.03 Hz) in the brain. A key question is whether/how the release of different neuromodulators during sleep is coordinated. In this study, we combined 2-site fiber photometry with electroencephalogram/electromyography recording to monitor the release of NE, 5-HT, and acetylcholine in the cortex and hippocampus during sleep and wake cycles. We found that the ISO of these neuromodulators is synchronized during NREM sleep. The synchrony between neuromodulatory systems increases in the oscillatory cycles leading to arousal. Furthermore, pharmacological inhibition of either the 5-HT or NE system eliminates the oscillation of other neuromodulators during NREM sleep. Optogenetic activation of 5-HT or NE neurons during NREM sleep induces the release of other neuromodulators in the absence of sleep-to-wake transitions. These results suggest that the rhythmic neuromodulator releases are highly coordinated in the brain. The synchrony among multiple neuromodulatory systems across brain regions provides a powerful neural mechanism to orchestrate sleep architecture and sleep-related neural processes.